How to break software a practical guide to testing - Whittaker, James A. (Addison Wesley, 2003)
CD-ROM contains: Canned HEAT v.2.0 -- Holodeck Lite v. 1.0.
Keywords: Computer software -- Testing; Bug -- Informatik; Softwaretest